The cysteine desulfurase, IscS, has a major role in in vivo Fe-S cluster formation in Escherichia coli - Schwartz, Christopher J. (The National Academy of Sciences, 2000)
The cysteine desulfurase, IscS, provides sulfur for Fe-S cluster synthesis in vitro, but a role for IscS in in vivo Fe-S cluster formation has yet to be established. To study the in vivo function of IscS in Escherichia coli, a strain lacking IscS was constructed and characterized. Using this iscS deletion strain, we have observed decreased specific activities for proteins containing [4Fe-4S] clusters from soluble (aconitase B, 6-phosphogluconate dehydratase, glutamate synthase, fumarase A, and FNR) and membrane-bound proteins (NADH dehydrogenase I and succinate dehydrogenase). A specific role for IscS in in vivo Fe-S cluster assembly was demonstrated by showing that an Fe-S cluster independent mutant of FNR is unaffected by the lack of IscS. These data support the conclusion that, via its cysteine desulfurase activity, IscS provides the sulfur that subsequently becomes incorporated during in vivo Fe-S cluster synthesis. We also have characterized a growth phenotype associated with the loss of IscS. Under aerobic conditions the deletion of IscS caused an auxotrophy for thiamine and nicotinic acid, whereas under anaerobic conditions, only nicotinic acid was required. The lack of IscS also had a general effect on the growth of E. coli because the iscS deletion strain grew at half the rate of wild type in many types of media even when the auxotrophies were satisfied.